Envisioning global LGBT human rights : (neo)colonialism, neoliberalism, resistance and hope - Nicol, Nancy (Human Rights Consortium, School of Advanced Study, University of London, 2018)
Envisioning Global LGBT Human Rights: (Neo)colonialism, Neoliberalism, Resistance and Hope is an outcome of a five-year international collaboration among partners that share a common legacy of British colonial laws that criminalise same-sex intimacy and gender identity/expression. The project sought to facilitate learning from each other and to create outcomes that would advance knowledge and social justice. The project was unique, combining research and writing with participatory documentary filmmaking. This visionary politics infuses the pages of the anthology. The chapters are bursting with invaluable first hand insights from leading activists at the forefront of some of the most fiercely fought battlegrounds of contemporary sexual politics in India, the Caribbean and Africa. As well, authors from Canada, Botswana and Kenya examine key turning points in the advancement of SOGI issues at the United Nations, and provide critical insights on LGBT asylum in Canada. Authors also speak to a need to reorient and decolonise queer studies, and turn a critical gaze northwards from the Global South. It is a book for activists and academics in a range of disciplines from postcolonial and sexualities studies to filmmaking, as well as for policy-makers and practitioners committed to envisioning, and working for, a better future.